The Arabic legal documents of Toledo: the merging of legal cultures in a society in transition - Daga Portillo, Rocio (Hispania sacra, 2024)
The Arabic documents from Toledo mirror a mosaic of laws and legal customs, together with the merging of laws and legal systems. Indeed, Christians, Muslims, and Jews of Toledo continued writing their legal documents in Arabic, following the pattern of Islamic administrative handbooks, for a period of more than two centuries subsequent to the Christian conquest of Toledo in 1085. By analysing three documents from the Toledo collection, two contracts of marriage and a testament while comparing them to the Islamic ones, the merging of two legal systems and cultures, the Visigothic and the Islamic one is demonstrated. The Toledo collection witnesses the continuity—but also discontinuity—of the notarial and legal Islamic culture. Castile legal system incorporated the Islamic structure and formulas of legal documents—even religious formulas such as Qur’anic quotations—, as well as legal customs or "laws" and notarial procedures within the framework of the Christian-Castilian law. At times, the formulas appear as Christian adaptations of Islamic ones, such as naming canon law "the Catholic Sharīʿa," al-Sharīʿa al-Qathūliqiyya. Toledo documents show a unique blending of legal cultures, demonstrating the close interaction of a European legal tradition with the Arabic-Islamic one. But, perhaps, the most striking aspect is that the Toledo documents portray the prominent role of women in the social and economic life of Toledo and challenge traditional perceptions of women´s roles in medieval societies.